QUALITY OF SURFACE WATERS OF HYDROGRAPHIC BASIN OF FORMOSO RIVER, BONITO - MS - Maximino Lelis, Leandro Reginaldo; Pinto, Andre Luiz; Silva, Priscila Varges da [UNESP]; Piroli, Edson Luis [UNESP]; Medeiros, Rafael Brugnolli; Gomes, Weslen Manari (Univ Estadual Paulista Julio Mesquita Filho, 2015)
Water is a natural resource essential for the survival of living beings. However, in addition, it also configures itself as a well with enormous political, economic and social value. In the municipality of Bonito, the water is even more important, given that 98% of the tourist attractions are related to this natural resource. In this context, this work aims to analyze the quality of surface waters of rivers of Formoso River Hydrographic Basin, which locate in the municipality of Bonito and characterize by the presence of several tourist enterprises. For the analysis of water quality were measured the following parameters: dissolved oxygen, electrical conductivity, turbidity, hydrogenionic potential, temperatures of air and water, total dissolved solids, redox potential and salinity. The water samples were collected at 42 distributed points in 11 tourist enterprises located in Formoso, Mimoso and Sucuri rivers. The results framed the surface waters of rivers researched of Hydrographic Basin of Formoso River in Class I, according to Resolution No. 357/2005 of CONAMA.
Keywords: Quality of Water; Hydrographic Basin of Formoso River; Bonito (MS)